IDENTIFIKASI LOKASI STRATEGIS UNTUK KAWASAN INDUSTRI DI KABUPATEN PURBALINGGA - Probo Hardini; Yanto Yanto; Yanuar Haryanto (Dinamika Rekayasa, 2007)
To reach the regional development equity, it is necessary to spread central activities in sub-region. This is a land use planning need to gain. According to development paradigms, industry is a leading sector that will influence its hinterland. This research was aims to know the strategic location for industrial area in Purbalingga, that have consideration in phisichal, economic, social, and stakeholders’ interest. The result indicate that industry should not located in central region as we saw in existing. The best alternative location for industrial area are Bukateja, Kutasari, Rembang, Mrebet, Karangreja , and Karangmoncol.